(3GdeSGMIs - (3YHO GdbGgQ Hf WGgQ Hf eMeO Hf YHO Gddg GdHZOGOj GdJejej GdCSaQGjjfj, CHh efUhQ,J (B429 (3g` s
(3ChdgG (B:s
(3HYO GdHSedI (B: (3EYde Cf eSGMI GdCQVjjf Ydi fhYjf (B: (3GdSGHW hGdLfI s
(3BNQgG (B:s
(3hYdi gPG bjGS GdHGH ` bGage Ef TGA Gddg JYGdi s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B48 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B309s
(3HQhcdeGf (B- (3GdLRA (B1 - (3U (B385 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA QjGVjGJ (B- (3bSe (B3 - (3U (B81 s
(3eUOQ GbJfGA GdCUd (B:s
(3dGdg di (B(2708) s
Keywords: (3GdQjGVjGJs